Computational studies on the conformational preference of N‐(Thiazol‐2‐yl) benzamide. Issue 10 (4th May 2020) - Zonouzi, Afsaneh; Kakeshpour, Ali; Ranjbar, Parviz Rashidi; Moradi, Ashraf
Abstract: N ‐(Thiazol‐2‐yl) benzamide 1 substructures are found in some of bioactive compounds. In some of protein/ligand co‐crystals, the 1 moiety adopts a conformer in which the amide O and the thiazole S atoms are close. In fact, in the crystalline structure of 1, the O—S distance is even shorter than Van der Waals radius. Although the natural bond orbital analysis finds a weak stabilizing interaction between O and S atoms, the attractive dipole–dipole interaction between the amide N─H and thiazole N atom seems to play a more significant role. Moreover, an intramolecular O—H hydrogen bonding in dimeric forms found to have an important role in the conformation preference of 1 . Computational details for the stability of conformers have been discussed using quantum theory of atoms in molecules, natural bond orbital (NBO) and noncovalent interaction index analysis. Abstract : N‐(Thiazol‐2‐yl) benzamide substructures are found in some protein/ligand co‐crystals. Although the natural bond orbital analysis finds a weak stabilizing interaction between O and S atoms, the attractive dipole‐dipole interaction between the amide N‐H and thiazole N atom seems to play a more significant role. Computational details for the stability of conformers have been discussed using QTAIM, NBO and NCI analysis.